PHYSIOTHERAPY MANAGEMENT OF 1/3 DISTAL FRACTURE OS RADIUS DEXTRA POST IMMOBILIZATION OF GIPS USING INFRARED(IR) MODALITIES AND THERAPY TRAINING AT EFARINA HOSPITAL ETAHAM BERASTAGI - Sumule, Usman; O.Brusa, jorge; Delfahedah Shofian, Yulia; Syarifuddin, Syarifuddin; Tony Sohdin Martua Simanjuntak, Edwin (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
Physiotherapy Management in Fracture Cases of 1/3 Distal Os Radius Dextra Post Immobilization of the Cast with Infrared(Ir) Modality and Exercise Therapy at Efarina Etaham Berastagi Hospital by producing patients with a diagnosis of fracture of the 1/3 distal os radius dextra post immobilization of the cast, after being carried out for 6 times of therapy with physiotherapy modalities, namely ir for 15 minutes and exercise therapy with resisted exercise methods, hold exercise and patient education, the results obtained are a decrease in pain, reduction of edema and muscle spasm, an increase in muscle strength and an increase in the ability of functional activity.